Efficacy of Leaf Extracts of Taphrosia purpurea and Catharanthus roseus against Root Rot Diseases of Chickpea (Cicer arietium L.) - and R. K. Nimbalkar2, M. S. Wadikar1*, (Recent Research in Science and Technology, 2010)
Abstract The efficacy of leaf extracts of Taphrosia purpurea and Catharanthus roseus against Macrophomina phaseolina and Sclerotium rolfsii the causal agents of root rot diseases of chickpea plants respectively were studied. A comparison between the in vitro activity of Taphrosia purpurea and Catharanthus rosesus, leaf extracts against these two pathogenic fungi were investigated. Two plant extracts tested for their fungitoxic activity gave significant inhibition of two pathogenic fungi at various concentration i. e 25, 50, 70,100% respectively. Keywords: Leaf extract, Taphrosia purpurea, Catharanthus roseus, Macrophomina phaseolina, Sclerotium rolfsii, Chickpea.